2006
DOI: 10.1097/01.brs.0000197865.20803.d4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Pedicle Screw Versus Hybrid Instrumentation in Posterior Spinal Fusion of Adolescent Idiopathic Scoliosis

Abstract: Pedicle screw instrumentation offers a significantly better major curve correction and postoperative pulmonary function values without neurologic problems compared with hybrid constructs. Both instrumentation methods offer similar junctional change, lowest instrumented vertebra, operative time, and postoperative SRS-24 outcome scores in the operative treatment of AIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
227
0
39

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 393 publications
(278 citation statements)
references
References 25 publications
12
227
0
39
Order By: Relevance
“…Some authors tried a combination of these two techniques and compared the results with pedicle screw systems and found similar results in terms of the junctional change, lowest instrumented vertebra, operative time and post-operative clinical outcome. However the pedicle screw system was still found to be superior in achieving a better major curve correction and lesser neurological complications [25].The risk can be minimized by better understanding of the anatomy and biomechanics involved in pedicle screw fixation [24,26,27]. The advantage of the hybrid system is that it can avoid the placement of pedicle screws in the upper thoracic spine, which is technically demanding and is fraught with the risk of neurological and vascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors tried a combination of these two techniques and compared the results with pedicle screw systems and found similar results in terms of the junctional change, lowest instrumented vertebra, operative time and post-operative clinical outcome. However the pedicle screw system was still found to be superior in achieving a better major curve correction and lesser neurological complications [25].The risk can be minimized by better understanding of the anatomy and biomechanics involved in pedicle screw fixation [24,26,27]. The advantage of the hybrid system is that it can avoid the placement of pedicle screws in the upper thoracic spine, which is technically demanding and is fraught with the risk of neurological and vascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…When pedicle screws are placed accurately, they should be completely contained within the pedicle, whereas hook insertion necessitates canal intrusion of approximately 30% [2]. Also, hooks are more prone to shift during correction maneuvers [8,9]. Another benefit of the more rigid stabilization offered by pedicle screw fixation is the ability to use shorter constructs to achieve deformity correction, thus preserving more motion segments than other techniques and potentially decreasing postoperative back pain [3,16,22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have been comprehensive surgeon-reported complication rates [1]; descriptions of particular complications, such as infections [11], superior mesenteric artery syndrome [4,13], etc; complications related to a certain technique, such as thoracoscopic treatment [8,10]; or complications compared between different techniques, such as hooks versus screws [5,6,12]. Our aim was to define a radiographic system of * P values were calculated using an overall chi square test for all treatment groups for existence of a serious radiographic adverse event (p = 0.427) or a radiographic adverse event (p = 0.88); no significant difference was found between the different surgical treatments; OASF = open anterior instrumented spinal fusion; TASF = thoracoscopic anterior instrumented spinal fusion; PSFH = posterior instrumented spinal fusion with an anchor system that utilized hooks or hooks, wires, and screws (hybrid systems); PSFS = posterior instrumented spinal fusion with an anchor system that utilized a majority of pedicle screws.…”
Section: Discussionmentioning
confidence: 99%